Avengers Assemble!: Critical Perspectives on the Marvel Cinematic Universe - McSweeney, Terence (Columbia University Press, 2018)
Avengers Assemble! explores the cinematic and televisual branches of the Marvel Cinematic Universe from a diverse range of critical perspectives. Beginning with Iron Man, it considers them as both embodiments of the changing blockbuster film and affective cultural artifacts that are immersed in the turbulent political climate of their era.
https://katalog.adlr.link/Record/76-EBC5552447